2006
DOI: 10.1161/01.hyp.0000219041.66702.45
|View full text |Cite
|
Sign up to set email alerts
|

Association Study With 33 Single-Nucleotide Polymorphisms in 11 Candidate Genes for Hypertension in Chinese

Abstract: Abstract-Essential hypertension is considered to be a typical complex disease with multifactorial etiology, which leads to inconsistent findings in genetic studies. One possibility of failure to replicate some single-locus results is that the underlying genetics of hypertension are not only based on multiple genes with minor effects but also on gene-gene interactions. To test this hypothesis, a case-control study was constructed in Chinese subjects, detecting both single locus and multilocus effects. Eleven ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
75
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(79 citation statements)
references
References 55 publications
2
75
2
Order By: Relevance
“…In Ghanaians, the two-locus model of angiotensin converting enzyme I/D and GRK4 65L predicts the hypertensive phenotype 70.5% of the time 37 . GRK4 variants, including 65L, 142V, and 486V, by themselves, or interaction with other variants of other genes are associated with hypertension in American Caucasians 39 , Australian Caucasians 12 , Italians 36 and northern Han Chinese 40 . We have reported that hGRK4γ 142V transgenic mice on 98% C57BL/6J background are hypertensive relative to non-transgenic littermates and hGRK4γ WT transgenic mice 6,8,11,13,34 .…”
Section: Discussionmentioning
confidence: 99%
“…In Ghanaians, the two-locus model of angiotensin converting enzyme I/D and GRK4 65L predicts the hypertensive phenotype 70.5% of the time 37 . GRK4 variants, including 65L, 142V, and 486V, by themselves, or interaction with other variants of other genes are associated with hypertension in American Caucasians 39 , Australian Caucasians 12 , Italians 36 and northern Han Chinese 40 . We have reported that hGRK4γ 142V transgenic mice on 98% C57BL/6J background are hypertensive relative to non-transgenic littermates and hGRK4γ WT transgenic mice 6,8,11,13,34 .…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]27,28 Of the 19 eligible articles, the study of Gu et al 28 was replaced by their earlier report, 10 as these two articles reported the same data. Wu et al 5 provided data on two Chinese minorities, the Hani and Yi, residents of the remote rural area of Yunnan, China.…”
Section: Selection Of Studiesmentioning
confidence: 99%
“…The underlying rationale of this inconsistency derives from the complexity of the genetic architecture, and must be explained in terms of heredity, variation and evolution. In addition, Gu et al 20 found that a potential interaction of CYP11B2-AGTR1 is involved in the etiology of hypertension. Against the background that the pathogenesis of essential hypertension is undefined, the question of whether secondary hypertension caused by PA follows a similar gene-gene interactive model is worthy of further research.…”
Section: Discussionmentioning
confidence: 99%